Motherhood and rheumatic disease – a balancing act. A qualitative study on the challenges of mothers with inflammatory arthritis - Nilssen, Ingrid Rekaa; Koksvik, Hege Svean; Jakobsen, Bente; Grønning, Kjersti (Frontiers in Lupus, 2024)
Objective: Inflammatory arthritis (IA) often come with symptoms of pain, stiffness and fatigue, as well as fluctuating and unpredictable disease patterns. All of these symptoms can cause challenges in the role as a mother for women with IA. The main objective of this study is to gain a broader understanding of how mothers with IA experience motherhood and the challenges they encounter within a biopsychosocial framework.The participants in this study were recruited through RevNatus, a Norwegian nationwide quality register. The sample consisted of women with IA who had given birth within the last 5 years. The data consisted of written answers to an open-ended question: "Is there anything, in particular, you have experienced as challenging with being a mother and having a rheumatic disease at the same time"? The data were analysed following Brinkmann and Kvale's qualitative content analysis.Results: 186 women answered the open-ended question. The responses consisted of a total of 9000 words. Motherhood with IA was described as a difficult balancing act, with practical and physical challenges affecting day-to-day life, medical dilemmas, as well as challenges on a deeper emotional level and worries for the future. The main finding in this study is that the challenges these women meet are multifactorial and complex, including physical, mental and social issues that have a large impact on their everyday life. Focusing solely on improving medical treatment will not solve the challenges these women face. A multidisciplinary approach and focus on patient education and self-management strategies is important to help these women thrive in their role as mothers with IA.